PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA MELALUI MEDIA FLASHCARD PADA MATA PELAJARAN BAHASA INDONESIA KELAS IV DI SDN 4 LIMBOTO BARAT - Riska R. Utina; Harni Jusuf; Sitti Rahmawati Talango (Al-mujahidah, 2026)
This study aims to determine the application of flashcard media in improving students' reading comprehension skills in Indonesian language subjects in grade IV of SDN 4 Limboto Barat. The type of research used is Classroom Action Research (CAR) which is carried out in two cycles. The research subjects are 20 students, consisting of 8 male students and 12 female students. Based on the results of the study after applying flashcard media, where student learning outcomes in cycle I meeting 1, 9 students (45%) completed and 11 students (55%) did not complete, then continued to cycle 1 meeting II where 11 students (55%) completed and 9 students (45%) did not complete. Because it has not achieved learning outcomes in accordance with the provisions, the researcher continued to Cycle II where in cycle II meeting 1, 14 students (70%) completed and 6 students (30%) did not complete. Then continued again in cycle II stage II where in cycle II meeting II, 18 students (90%) completed and 2 students (10%) did not complete. Thus, the application of flashcard media in learning Indonesian language material on short stories can improve the reading comprehension skills of fourth grade students at SDN 4 Limboto Barat.